STANDARDIZATION OF HPLC METHOD OF SCOPOLETIN IN DIFFERENT EXTRACTS OF CONVOLVULUS PLURICAULIS (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Different extract of Convolvulus pluricaulis choisy, (Methanol, hydro-alcohol (50%) and water) were prepared and tested of scopoletin. The maximum scopoletin content was observed in 50% ethanolic extract followed by methanol and water extracts. It was 0.1738%, 0.0932% and 0.0435% in hydro-alcoholic, Methanol and water extract respectively. A simple HPLC (High Performance Liquid Chromatography) was developed for the determination of Scopoletin in Convolvulus pluricaulis choisy. Shankhpushpi is an astringent, hot aphrodisiac and a nervine tonic. It improves strength, digestive power, helpful in epilepsy, insomnia, heart disease and hemetemesis. Analyte separation and quantification were achieved by high-performance liquid chromatography (HPLC) and UV detection at 366 nm. The method involves the use of C18 column (Phenomenex, 250 mm × 4.6 mm, 5µm) with isocratic mixture of methanol and water containing 0.1% v/v formic acid in the ration of 30:70. Linearity was observed in the range of 20-100 ppm with correlation coefficient of 0.9961. Relative standard deviation of linearity of the method was found to be 1.29%. Detection limit was 5.0 ppm and quantification limit was 7.5 ppm. The repeatability of the method was found to be 0.71%. Recovery values from 99.10 to 100.1% indicate best accuracy of the method.